Business principles. (Academic Video Online, 2013)
Dallas County Community College District - Continuing Education/Noncredit Courses: In addition to college credit classes, this video was designed to improve your business skills -- if you dream of owning your own business or help you become the corporate executive you want to be. These Continuing Education (CE)/Noncredit courses do not offer college credit but may apply toward industry credentials or other workplace certificates. In this course module: Successful entrepreneurs share their financial planning process.